Integrating The Social Dimension Of ESG Into Circular Business Model Transformations - Macher, Gergely Zoltán; Szigeti, Cecília (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The transition towards circular economy business models is increasingly framed as a key instrument for achieving environmental sustainability and long-term economic resilience. However, the social dimension of sustainability within circular transformations remains underexplored in both academic research and corporate practice, despite its growing relevance in ESG frameworks. This paper addresses this gap by examining how social sustainability can be embedded into circular business model transformations in order to generate social as well as environmental value. Furthermore, the paper explores stakeholder engagement mechanisms within circular value chains, focusing on the involvement of employees and local communities as key contributors to socially inclusive circular practices. Finally, the alignment between corporate governance structures and social sustainability objectives is analysed, highlighting how governance mechanisms can facilitate the integration of social considerations into circular strategies. The paper links circular business model innovation with ESG social performance, contributing to sustainability and management literature.